2019
DOI: 10.1097/aog.0000000000003502
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification of Fetal Cardiac Anomalies in an Underserved Population Using Telecardiology

Abstract: OBJECTIVE: To evaluate a fetal telecardiology program in a medically underserved area. METHODS: We conducted a prospective case series of pregnant women at 18–38 weeks of gestation with risk factors for fetal congenital heart disease. Obstetric ultrasonographers performed fetal echocardiograms (local site) that were read in real time. The results were given to the mother by a fetal cardiologist at a children's hospital 243 miles and two mountain passes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…Multiple studies have evaluated the use of video calls in rural areas to aid in fetal cardiac evaluations and also to connect regional specialists with local providers to give guidance on necessary procedures. Both applications have demonstrated decreased travel time and costs, with some studies citing up to a ninefold decrease in expenditures for pregnant individuals in rural settings, with no evidence of harm or decrease in quality of care (24,44). More recent evolving applications of telemedicine within obstetrics involve the use of remote monitoring devices.…”
Section: Pregnancymentioning
confidence: 99%
“…Multiple studies have evaluated the use of video calls in rural areas to aid in fetal cardiac evaluations and also to connect regional specialists with local providers to give guidance on necessary procedures. Both applications have demonstrated decreased travel time and costs, with some studies citing up to a ninefold decrease in expenditures for pregnant individuals in rural settings, with no evidence of harm or decrease in quality of care (24,44). More recent evolving applications of telemedicine within obstetrics involve the use of remote monitoring devices.…”
Section: Pregnancymentioning
confidence: 99%
“…For example, use of telecardiology showed that all foetuses with congenital heart disease (CHD) were correctly risk-stratified for delivery. 9 The cost of POCUS is a major economic aspect in developing countries as it is deemed suitable only if leading to similar outcomes but with lower expenses as compared to current obstetric examination. 10 Therefore, training and application of POCUS have to reflect the needs of the specific communities and must be tailored accordingly.…”
Section: Point-of-care Testing Related To Maternal and Neonatal Carementioning
confidence: 99%
“…The initial use involved transmitting ultrasound images via the nascent internet to obtain a second expert opinion regarding concern for fetal anatomic anomaly [1]. Since then, many have used telemedicine visits to provide consultation to those in a rural setting far removed from tertiary care with positive outcomes and patient satisfaction [2][3][4]. This modality of providing care did not reach general consciousness until 2020 due to the coronavirus disease 2019 (COVID-19) pandemic.…”
Section: Introductionmentioning
confidence: 99%